Level of Eating Parenting Patterns on The Incident of Diarrhea in Children Toddlers in Puupi Village, Kolono District, South Konawe District, Southeast Sulawesi - Khodija, Unziya; Werdini, Yoessy Etna; Askaruddin, A (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study aimed to determine the relationship of knowledge, attitudes and parenting food on the incidence of diarrhea in children in the village Toddler Puupi District Kolono Konsel Southeast.This research is the design of Analytical Deskripstif cross sectional study design and in the Village District Puupi Kolono. The population in this study were all mothers with children under five are enrolled in Puupi village of 102 people and a sample of 102 people were taken using the Total Sampling, data obtained using a questionnaire and tested using Chi-Square test. Methodology: The type of research used is analytical descriptive research, namely research that aims to analyze the relationship between the dependent variable and the independent variable. The research design used is a Cross Sectional Study, namely research carried out at the same time and place Results: The results obtained from 55 children under five with diarrhea, most of which is 72.7% less in the category of mother's knowledge, attitudes mother in 63.6% and 67.3% less category parenting category eating less later than 47 children under five who not experience diarrhea, which is 51.1% majority in the category of sufficient knowledge of her mother, her mother's 61.7% in the category of pretty, 62.7% in the parenting category eating enough. Applications/Originality/Value: The novelty of this research is the research location and sample and number of studies.